SWOT Analysis on Marketing Strategy in Mutiara Swalayan Minimarket Medan - Filbert; Sembiring, Anita Christine; Antoni, Jufri (Journal Knowledge Industrial Engineering (JKIE), 2024)
Mutiara Swalayan, a minimarket selling various products like basic necessities, faces challenges in maintaining high-quality production due to competition. This study identifies and analyzes competition that occurs using the method of SWOT Analysis, the study reveals that Strength of the minimarket account for 2.03. Additionally, Weakness obtained for 1.98, Opportunity and Threats respectively 2.12 and 2.10 The result of this research obtained weighting IFE score of 4.01 while EFE obtained score weighting of 4.22.This research provides insights to improve productivity and develop a growth strategy for Mutiara Swalayan, focusing on effective marketing strategies to boost competitiveness and market position. The impact of this study lies in its ability to offer practical recommendations that enhance the minimarket's resilience against competitive pressures, ultimately leading to sustainable business growth and stronger market presence.